Optimasi produksi tanaman untuk petani transmigran - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1981)
ABSTRAK A model for optimizing crop production in transmigration area, where farmers have a lirnitedala.nds (about two hectares) was developed .0 sing a multistage programming the model try to optimize farmer's net income through :(1) optimizing the management packages for each crop, and (2) optimizing the land allocation It is belief that in some cases the model is not fitted. However, at least this can be used as a starting point in looking for a better solution on developing the transmigration areas. Key word: musim tanam, produksi tanaman, pola tanam